Towards understanding the triggering of the malignant cell death in high-efficiency magneto-mechanical anticancer therapy - Semina, P. N.; Isaev, I. L.; Komogortsev, S. V.; Klyuchantsev, A. B.; Kostyukov, A. S.; Blagodatova, A. V.; Khrennikov, D. E.; Kichkailo, Anna S.; Zamay, Tatiana N.; Lapin, Ivan N.; Sokolov, Alexey E.; Polyutov, S. P.; et al. (Journal of physics D: Applied physics)
The paper discusses schemes for implementing magneto-mechanical anticancer therapy and the most probable scenarios of damaging mechanical effects on the membranes of malignant cells by targeted magnetic nanoparticles (MNPs) selectively bound to membrane mechanoreceptors employing aptamers. The conditions for the selective triggering of the malignant cell apoptosis in a low-frequency non-heating alternating magnetic field, corresponding to the exceeding threshold value of the force acting on the membrane and its mechanoreceptors, are established using a nanoparticle dynamic simulation. The requirements for the functionality of MNPs and their suitability for biomedical applications are analyzed. Attention is paid to the possibility of the formation of magnetite nanoparticle aggregates in an external magnetic field and their localization near tumor cell membranes. It is shown that the scenario involving the process of aggregation of magnetite nanoparticles provides a sufficient magneto-mechanical impact to achieve a therapeutic effect. A possible explanation for the experimentally established fact of successful application of magneto-mechanical therapy using magnetite nanoparticles is presented, in which complete suppression of the Ehrlich carcinoma in an alternating magnetic field as a response to a magneto-mechanical stimulus was demonstrated. This result confirmed the possibility of using the method for high efficiency treatment of malignant neoplasms. The paper provides an extensive review of key publications and the state of the art in this area.